Stabilization of Fibrous Peat Soils with Addition Palm Shell Ash Waste - Deli Oktopani; Yulindasari Sutejo; Febrian Hadinata (Publikasi Indonesia, 2024)
South Sumatra Province has a peat area of 1.4 million Ha. The distribution of peat soil in Ogan Ilir is 23,687.91 Ha. Peat soil has a low bearing capacity. This research aims to explain the effect of stabilization on peat soil characteristics. Peat soil samples were taken using the Block Sampling method. The research locations are Parit Village and Lorok Village, Ogan Ilir Regency. Peat soil needs better properties and is unsuitable for foundation soil for civil construction. To overcome this, one method of soil improvement is required, namely the chemical stabilization method: changing the chemical properties of the soil by adding a mixture. The mixture used is palm shell ash waste with variations of 0%, 10%, 15%, 20%, 25%. Soil properties (physical and chemical), SEM, EDS, PTS, and CBR tests were carried out to determine the effect of this mixture. Soil properties test results: water content () in Parit Village 226.39%, and Lorok Village 252.39%. The fiber content (FC) test results for Parit Village were 25.18% and for Lorok Village 28.01%. Peat soil is classified as fibrous peat soil. The CBR value for Parit Village was 4.60%, and Lorok Village was 4.16%. The results of the immersion CBR test showed that Parit Village had a curing period of 7 days, a variation of 5%, namely 4.68%. Look Village obtained the most outstanding results: a curing period of 14 days, a variation of 25%, and 4.76%. The CBR value obtained in this study is 3%-5% (average) when used for subgrade strength with compaction conditions depending on the road category.